Development of Learning Media for Speaking Course A1 Daily Life and Family Theme - Nabila Azzahra; Suci Pujiastuti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the development of animated videos as a learning medium for A1 speaking. This study focuses on making animated videos. This study uses a descriptive qualitative method with data collection through online questionnaires and direct interviews. This study is a study that uses the 4D model. This research model consists of 4 steps, namely: 1) Define, 2) Design, 3) Develop, 4) Disseminate. The result of this study is an animated video with German subtitles. This video is 6:49 minutes long and in MP4 format. This video has been validated by media experts with a score of 93.75.